Annual Plan 1994-95 Statements Government of Manipur - Planning Commission (Planning Commission, 1993)
Abstract of Financial Outlays and Expenditure for 8th Plan 1992- 97 and Annual Plan 1994-95 Progress of Expenditure During the Annual Plan 1993- 94 and Proposed outlay for the Annual Plan 1994-95 Physical Targets and Achievements during the Annual Plan 1993-94 and Proposals for the Annual Plan 1994-95 Proposals for Spill over and ongoing programmes/projects Proposals for Maximising Benefits of completed programmes/projects(As the 31.3.1994) Proposals for programmes/projects - New Schemes of Eighth Plan Summary Statement -Proposals for Programmes/Projects Statement Regarding Externally Aided Projects Annual Plan 1994-95 Outlays By heads of Development(For District Plans) Centrally Sponsored Schemes.
Government of Manipur, Planning Department